2013
DOI: 10.1177/0305735613482023
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of compositional structure and performance expression to the communication of emotion in music

Abstract: In this investigation, eight highly-trained musicians communicated emotions through composition, performance expression, or the combination of the two. In the performance condition, they performed melodies with the intention of expressing six target emotions: anger, fear, happiness, neutral, sadness, and tenderness. In the composition condition, they composed melodies to express the same six emotions. The notated compositions were then played digitally without performance expression. In the combined condition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 51 publications
5
48
0
1
Order By: Relevance
“…Thus, whereas previous studies have found that pitch-based cues such as pitch height, pitch range, pitch variability, and modality contribute to emotional communication (Ilie and Thompson, 2006; Gabrielsson and Lindström, 2010; Quinto et al, in press), MIV does not appear to be involved in the communication of emotion in music. Nonetheless, recent investigations suggest that features considered to be music-specific, including interval size and mode, may actually play a role in emotional speech (Bowling et al, 2010; Curtis and Bharucha, 2010).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, whereas previous studies have found that pitch-based cues such as pitch height, pitch range, pitch variability, and modality contribute to emotional communication (Ilie and Thompson, 2006; Gabrielsson and Lindström, 2010; Quinto et al, in press), MIV does not appear to be involved in the communication of emotion in music. Nonetheless, recent investigations suggest that features considered to be music-specific, including interval size and mode, may actually play a role in emotional speech (Bowling et al, 2010; Curtis and Bharucha, 2010).…”
Section: Discussionmentioning
confidence: 61%
“…There was also a trend whereby the average interval size was larger for pieces expressing happiness than for pieces expressing sadness. Additional details can be found in Thompson et al (2012) and Quinto et al (in press). …”
Section: Methodsmentioning
confidence: 99%
“…Quinto et al (2013) found that there were no differences in overall emotional decoding between instruments, but other results suggest that certain instruments constrain the range of emotions that can be conveyed (Schutz et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…In the perfonnance condition, emotionally ambiguous melodic fragments were composed by one of the authors and supplied to musicians, who performed them with the intention of expressing the six target emotions. Quinto et al (2013) used a forced-choice paradigm that focused on decoding accuracy for the same stimuli. They found that some emotions were well decoded through composition (e.g., fear), whereas other emotions were well decoded through performance (e.g., anger, sadness).…”
mentioning
confidence: 99%
“…There is debate over whether meanings are universal or specific to individuals or contexts (Erkkilä et al 2012;Pavlicevic 1997) and research on emotional expression in musical performance continues to find that emotions other than basic categories are less clearly communicable (Gabrielsson and Juslin 1996;Quinto et al 2014), even between music therapists (Gilboa et al 2006). In the fixed-choice paradigm of such experimental work the listener recognises or rates predetermined monolithic emotional categories, whereas a therapist seeks to apprehend and respond non-verbally to a client's emotional state at a more holistic level through improvising.…”
Section: D) Emotional Expressionmentioning
confidence: 99%